2012
DOI: 10.1038/hr.2012.60
|View full text |Cite
|
Sign up to set email alerts
|

Epistasis among eNOS, MMP-9 and VEGF maternal genotypes in hypertensive disorders of pregnancy

Abstract: Polymorphisms of the endothelial nitric oxide synthase (eNOS), matrix metalloproteinase-9 (MMP-9) and vascular endothelial growth factor (VEGF) genes were shown to be associated with hypertensive disorders of pregnancy. However, epistasis is suggested to be an important component of the genetic susceptibility to preeclampsia (PE). The aim of this study was to characterize the interactions among these genes in PE and gestational hypertension (GH). Seven clinically relevant polymorphisms of eNOS (T-786C, rs20707… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 41 publications
0
17
0
2
Order By: Relevance
“…Contrary to this finding, the same variant of this MMP-9 polymorphism has been associated with a higher risk of gestational hypertension and preeclampsia in Kurdish and Chinese population [ 51 , 52 ]; also, some results suggest that this polymorphism may affect the therapeutic response to antihypertensive agents, concluding that this MMP-9 variant could help to identify those patients with a refractory response [ 37 ]. Additionally, Luizon et al reported that the combination of genotypes MMP-9-1562CC with VEGF-634CC or MMP-9-1562CT with VEGF-634CC or -634GG were significantly more frequent in women with preeclampsia than in normal pregnant women, and results suggest that these epistasis contribute to a higher susceptibility to developing preeclampsia [ 53 ]. Different results were reported in Brazilian and British women, where the MMP-9-1562 C/T polymorphism was not associated with the syndrome [ 54 , 55 ].…”
Section: Mmps As New Biomarkers and Potential Biological Targets Imentioning
confidence: 99%
“…Contrary to this finding, the same variant of this MMP-9 polymorphism has been associated with a higher risk of gestational hypertension and preeclampsia in Kurdish and Chinese population [ 51 , 52 ]; also, some results suggest that this polymorphism may affect the therapeutic response to antihypertensive agents, concluding that this MMP-9 variant could help to identify those patients with a refractory response [ 37 ]. Additionally, Luizon et al reported that the combination of genotypes MMP-9-1562CC with VEGF-634CC or MMP-9-1562CT with VEGF-634CC or -634GG were significantly more frequent in women with preeclampsia than in normal pregnant women, and results suggest that these epistasis contribute to a higher susceptibility to developing preeclampsia [ 53 ]. Different results were reported in Brazilian and British women, where the MMP-9-1562 C/T polymorphism was not associated with the syndrome [ 54 , 55 ].…”
Section: Mmps As New Biomarkers and Potential Biological Targets Imentioning
confidence: 99%
“…These findings are relevant because the associated genetic markers may allow early detection of patients at increased risk of hypertensive disorders of pregnancy, which increase morbidity and mortality. 41 The present study has other limitations. First, we studied a relatively small number of patients and plasma visfatin/NAMPT levels were determined in a smaller number of patients.…”
Section: Discussionmentioning
confidence: 79%
“…Although no significant association between VEGF +936 T allele and PE was observed in the study by Cunha et al ., the frequency of the VEGF ‐2578A allele was significantly higher in the control group . In another study, the combination of MMP ‐9 ‐1562CC with VEGF ‐634GG genotypes was more frequent in control women compared to PE women . Chedraui et al .…”
Section: Discussionmentioning
confidence: 92%